Ship-based observations of atmospheric potential oxygen and regional air–sea O2 flux in the northern North Pacific and the Arctic Ocean. Issue 1 (1st December 2016) - Ishidoya, Shigeyuki; Uchida, Hiroshi; Sasano, Daisuke; Kosugi, Naohiro; Taguchi, Shoichi; Ishii, Masao; Morimoto, Shinji; Tohjima, Yasunori; Nishino, Shigeto; Murayama, Shohei; Aoki, Shuji; Ishijima, Kentaro; et al.
Abstract : Simultaneous observations of atmospheric potential oxygen (APO=O2 +1.1×CO2 ) and air–sea O2 flux, derived from dissolved oxygen in surface seawater, were carried out onboard the research vessel MIRAI in the northern North Pacific and the Arctic Ocean in the autumns of 2012–2014. A simulation of the APO was also carried out using a three-dimensional atmospheric transport model that incorporated a monthly air–sea O2 flux climatology. By comparing the observed and simulated APO, as well as the observed and climatological air–sea O2 fluxes, it was found that the large day-to-day variation in the observed APO can be attributed to the day-to-day variation in the local air–sea O2 fluxes around the observation sites. It was also found that the average value of the observed air–sea O2 fluxes was systematically higher than that of the climatological O2 flux. This could explain the discrepancy between the observed and simulated seasonal APO cycles widely seen at various northern hemispheric observational sites in the fall season.